Pengukuran Kinerja Dinas Kebudayaan, Pariwisata, Kepemudaan, Dan Olahraga Kota Cimahi Dengan Pendekatan Balanced Scorecard - Dillah Nur Laila; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research aims to measure the performance of the Ministry of Culture, Tourism, Youth, and Sports (Disbudparpora) cimahi city by using a balanced scorecard approach. Performance measurement is based on four balanced scorecard perspectives, namely financial, customer, internal business process, and growth and learning. This type of research is quantitative descriptive research. Data collection using documentation methods, questionnaires, and interviews. The financial perspective is measured using Regulation of the Peraturan Menteri Keuangan (PMK) No. 214 of 2017, while the non-financial perspective is measured by the Likert Scale (five scales). The results of this study show that: (1) The performance of the financial perspective is less good in terms of budget absorption, very efficient in terms of efficiency ratio, and less effective in terms of effectiveness ratio, (2) The performance of the customer's perspective is quite satisfactory, (3) The performance of the internal business process perspective is very satisfactory, (4) The performance of the learning and growth perspective is quite satisfactory. (5) The overall performance is quite good.